2018
DOI: 10.1136/tobaccocontrol-2018-054463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact and equity of a tobacco-free pharmacy law on retailer density in New York City neighbourhoods

Abstract: NYC's tobacco-free pharmacy law substantially reduces tobacco retailer density overall, but the impact is not equal across neighbourhoods. In order to minimise disparities in the tobacco retail environment, local governments considering a similar ban should supplement this strategy with other retailer restrictions to achieve equitable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…We found that there was a lower odds of a tract having a tobacco-selling pharmacy in neighborhoods with a greater percentage of Black or Hispanic or Latino residents in adjusted models, suggesting that policies that restrict the sales of tobacco products in pharmacies may not decrease the number of tobacco retailers equitably across neighborhoods. These findings are consistent with other studies that have investigated the impact of a pharmacy ban on inequities in tobacco retailer density ( Craigmile et al, 2020 ; Giovenco et al, 2019 ; Kulbicki & Leslie, 2015 ; Tucker-Seeley et al, 2016 ). While our study sample was limited to pharmacies that sell tobacco products, our findings are similar to those focused on pharmacy deserts, which find that pharmacies are less available in neighborhoods with a greater proportion of some racially and ethnically minoritized groups ( Qato et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that there was a lower odds of a tract having a tobacco-selling pharmacy in neighborhoods with a greater percentage of Black or Hispanic or Latino residents in adjusted models, suggesting that policies that restrict the sales of tobacco products in pharmacies may not decrease the number of tobacco retailers equitably across neighborhoods. These findings are consistent with other studies that have investigated the impact of a pharmacy ban on inequities in tobacco retailer density ( Craigmile et al, 2020 ; Giovenco et al, 2019 ; Kulbicki & Leslie, 2015 ; Tucker-Seeley et al, 2016 ). While our study sample was limited to pharmacies that sell tobacco products, our findings are similar to those focused on pharmacy deserts, which find that pharmacies are less available in neighborhoods with a greater proportion of some racially and ethnically minoritized groups ( Qato et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies in select U.S. cities and states also suggest that the impact of policies that prohibit pharmacies from selling tobacco products may not be equitable ( Craigmile et al, 2020 ; Giovenco et al, 2019 ; Hall et al, 2019 ; Kulbicki & Leslie, 2015 ). Additionally, some places have implemented policies that only allow specialty tobacco shops to sell tobacco products or certain types of tobacco products ( CounterTobacco.org, 2020 ).…”
mentioning
confidence: 99%
“… 63 65–67 69 For the first time, three studies reported on the equity impact of retailer bans, with one covering menthol cigarettes sales near schools 57 and two covering sales of tobacco products by pharmacies. 60 68 The largest shift in intervention type related to population-level cessation support. Where in 2014, two-thirds of studies looked at provision of combined behavioural and pharmacological support (primarily by specialist services), here the focus was on brief interventions within primary care 73–77 82 or access to free or low-cost cessation medication.…”
Section: Resultsmentioning
confidence: 99%
“…Thus—for example—Huang and colleagues 42 noted that the effect of local smoke-free policies may be influenced by both state-level tobacco control programmes and the specific characteristics of the local population. Two studies exploring the equity impact of bans on pharmacies selling tobacco products (one state level 68 and one city level 60 ) found that equity effects were dependent on the socially patterned distribution of pharmacies. Zhang et al , 35 in contrast, evaluated the impact of three different interventions (tobacco tax, smoke-free laws and media campaigns) on home smoking bans, assessing their effects both separately and jointly, and finding that the equity-positive effect of smoke-free laws was no longer apparent in the multi-policy analysis.…”
Section: Discussionmentioning
confidence: 99%
“…By March 2018, 171 cities (the majority located in Massachusetts) had enacted tobacco-free pharmacy ordinances, less than 1% of US municipalities,24 25 and in July 2018, Massachusetts prohibited tobacco sales in pharmacies statewide 26. Studies suggest that tobacco-free pharmacies reduce retailer density,27–29 and this reduced density leads to lower smoking initiation and prevalence 30–38. Survey research has shown that both pharmacists and the general community support tobacco-free pharmacies after implementation,2 16 and media coverage has been favourable 39.…”
Section: Introductionmentioning
confidence: 99%